EVALUATION OF THE CONFORMITY OF CARDIOVASCULAR THERAPY TO CURRENT CLINICAL GUIDELINES IN THE IMPROVEMENT OF OUTCOMES IN PATIENTS AFTER STROKE (ACCORDING TO THE LIS-2 REGISTER) - A. Yu. Suvorov; S. Yu. Martsevich; N. P. Kutishenko; A. D. Deev; M. L. Ginzburg; A. V. Akimova; E. V. Daniels; A. V. Fokina; N. A. Dmitrieva; L. Yu. Drozdova; N. Yu. Zhuravskaya; O. V. Lerman; et al. (Столичная издательская компания, 2015)
Aim. To study the conformity of preventative therapy prescribed to patients during a hospital stay and at a discharge to clinical guidelines using a special algorithm, and to assess the impact of the results on a long-term mortality based on the LIS-2 register (Lyubertsy study of mortality in patients after cerebral stroke). Material and methods. The scales to assess the quality of cardiovascular care for the prevention of recurrent stroke along with the prevention of recurrent ischemic attacks index (PRIA index) for this assessment were developed according to current clinical guidelines. Analysis of the therapy was performed using PRIA index on survived hospital patients from LIS-2 register (N=753). The impact of PRIA index results on a long-term mortality (Me=2.3 years) was studied. Results. Based upon the results of the assessment obtained with PRIA index, higher treatment conformity to clinical guidelines resulted in a significantly better long-term survival. Non-conformity to clinical guidelines was due to the lack of prescription of drugs with proven efficacy and irrational choice of preventive therapy. Median of treatment quality assessment was 44.4% (22.2; 44.4). Conclusion. Low conformity of preventive therapy to clinical guidelines is found in the LIS-2 register. The algorithm for the assessment of preventive cardiovascular therapy quality allows identifying limitations in the prevention of recurrent stroke, and can serve as an example of implementation of evidence-based medicine in clinical practice.